Motivations and Barriers for Sheep and Goat Meat Consumption in Europe: A Means–End Chain Study - Mandolesi, Serena; Naspetti, Simona; Arsenos, Georgios; Caramelle-Holtz, Emmanuelle; Latvala, Terhi; Martin-Collado, Daniel; Orsini, Stefano; Ozturk, Emel; Zanoli, Raffaele (MDPI AG, 2020)
This international study involving seven European countries (Italy, UK, Finland, France, Spain, Greece, Turkey) was conducted to explore the relevant reasons that affect both consumer and non-consumer perceptions of sheep and goat meat. Laddering and means–end chain theory were applied. The results indicate that consumers associate sheep and goat meat with a unique taste, authenticity and natural production, linked with values such as health and enjoyment of life. In contrast, non-consumers mainly feel disgusted when they think and feel about these meats, and do not associate any specific health benefits to their consumption, disliking their taste, odour and fat content. This study is based on qualitative research. Only analytical generalizations are possible, expanding the theory on what drives consumer behaviour when purchasing meat. No previous means–end chain studies are available in the literature regarding small ruminants’ meat consumer preferences.
Keywords: laddering; consumer attitudes; meat; food consumption; small ruminants; consumer perceptions